Harrington Putnam papers - Putnam, Harrington, 1851-1937.
Notebooks relating to Putnam's career as justice of the Supreme Court of New York and to cases heard by the court. Also includes an index of evidence and correspondence with Sir G.G. Greenwood pertaining to Shakespeare scholarship.
Jurist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Greenwood, G. G. -- Sir, -- 1850-1928 -- Correspondence; Shakespeare, William, -- 1564-1616 -- Study and teaching; New York (State). -- Supreme Court; Courts -- New York (State); Jurists